What images do - Bäcklund, Jan 1966-; Renner, Michael 1961-; Søberg, Martin 1978- (Aarhus University Press, 2019)
When images look like something they do so because they are different from what they resemble. This difference is not sufficiently captured by the traditional theories of representation and mimesis, and yet it is the condition for any such theory. Various contemporary image theorists have pointed out that Plato already understood that images are not what they look like. Images have their own existence, which cannot be identified with a concept, but should be examined in terms of actions.0This book comprises fifteen articles that investigate what images do, particularly in relation to the disciplines of architecture, design and visual arts. It claims that it is the differentiating power of images - their actions - which constitutes their capacity to look like something they are not, as well as create something that does not yet exist. What Images Do address the crucial role that images might play in producing and investigating what we have not yet seen or understood in and of reality.